Changes in hormonal balance as key to reserve degradation after dormancy overcoming in Annona macroprophyllata and Annona purpurea seeds - Ferreira, Gisela [UNESP]; De-La-cruz-chacón, Ivan; González-Esquinca, Alma Rosa (FapUNIFESP (SciELO), 2020)
Studies on the effect of the applying of phytoregulators to overcome seed dormancy have been carried out in Annonaceae species, thus the endogenous relationship between abscisic acid and gibberellins after the application of phytoregulators needs to be known in these species. Considering the importance of hormonal balance in dormancy mechanisms, the aim of this research was to elucidate how endogenous ABA and GA concentrations change after the application of phytoregulators in seeds and how these changes affect reserve degradation during germination of Annona macroprophyllata and A. purpurea seeds. Seeds were submitted to three conditions:-no soaking, soaking-in-water and soaking-in-GA4+7 +benzyladenine. ABA, GA, lipids, proteins, and total soluble sugars were quantified at 0, 2, 5, 10, and 15 days after the beginning of treatments. The application of phytoregulators led change of the hormonal balance inducing increase in endogenous GA and reduction in ABA levels since seed soaking. During imbibition, the degradation of seed reserves (breaks proteins first, and then soluble sugars and finally lipids) was observed and complete germination was obtained after 10 days, with primary root emission. In both species, dormancy can be broken soon after seed dispersal when the balance between GA and ABA is endogenously changed (by exogenous application of phytoregulators), leading to metabolic reserve degradation and germination.
Câmbios no balanço hormonal como chave para degradação de reservas após a superação da dormência de sementes de Annona macroprophyllata e Annona purpurea
Keywords: Abscisic acid; Germination; Gibberellins; Lipids; Phytoregulators; Plant growth regulators; Proteins; Soluble sugars